2003
DOI: 10.1029/2002tc001383
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the early Mesozoic blueschist‐bearing Qiangtang metamorphic belt, central Tibet

Abstract: [1] A >500-km-long east-west trending metamorphic belt in the Qiangtang terrane of central Tibet consists of tectonic melange that occurs in the footwalls of Late Triassic -Early Jurassic domal low-angle normal faults. The melange is comprised of a strongly deformed matrix of metasedimentary and mafic schists that encloses lesser-deformed blocks of metabasites, Carboniferous-Triassic metasedimentary rocks, and early Paleozoic gneiss. Both the blocks and melange matrix exhibit greenschist, epidoteblueschist, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
391
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(419 citation statements)
references
References 80 publications
(155 reference statements)
12
391
0
2
Order By: Relevance
“…10), as suggested by some previous workers based on tectonic, sedimentary, metamorphic and paleomagnetic analyses (e.g., Kapp et al, 2003;Nie et al, 1994;Reid et al, 2007;Roger et al, 2003;Yin and Harrison, 2000). With the ongoing double-sided subduction, the eastern Songpan-Ganzi oceanic basin diminished in size or even disappeared, and collisions between different blocks or arc fragments (e.g., the South China, Kunlun-Qaidam, North China, South Qinling, Qilian, Yidun, and Qiangtang Blocks; Fig.…”
Section: Tectonic Implicationsmentioning
confidence: 69%
“…10), as suggested by some previous workers based on tectonic, sedimentary, metamorphic and paleomagnetic analyses (e.g., Kapp et al, 2003;Nie et al, 1994;Reid et al, 2007;Roger et al, 2003;Yin and Harrison, 2000). With the ongoing double-sided subduction, the eastern Songpan-Ganzi oceanic basin diminished in size or even disappeared, and collisions between different blocks or arc fragments (e.g., the South China, Kunlun-Qaidam, North China, South Qinling, Qilian, Yidun, and Qiangtang Blocks; Fig.…”
Section: Tectonic Implicationsmentioning
confidence: 69%
“…1a, b). It is a tectonic complex composed of blueschist, eclogite, ophiolite, OIB-type basalt, metasedimentary rocks, and minor chert (BGMR, 1993;Li et al, 1995Li et al, , 2006Li et al, , 2008Kapp et al, 2000Kapp et al, , 2003Zhang et al, 2010aZhang et al, , 2010bZhang et al, , 2010cZhang et al, , 2014Zhai et al, 2007Zhai et al, , 2011aZhai et al, , 2011b. The ophiolitic mélange in the LSSZ consists mainly of ultramafic rocks, gabbro, basalt, pillow lava, and minor chert (Zhai et al, 2013).…”
Section: Regional Settingmentioning
confidence: 99%
“…The ocean was suggested to have closed during the Triassic based on the presence of the Triassic high-pressure metamorphic rocks belt in the central Qiangtang (Zhai et al, 2011a(Zhai et al, , 2011b(Zhai et al, , 2013. However, Kapp et al (2000Kapp et al ( , 2003 suggested that the Longmu-Shuanghu metamorphic rocks belt was only a metamorphic core complex produced by underthrusting of Jinshajiang ocean lithosphere beneath the Qiangtang Terrane during the Early Mesozoic, then to be exhumed in an intracontinental setting by Late Triassic-Early Jurassic normal faulting. Recently, Zeng et al (2015) proposed that the exhumation of Triassic Qiangtang metamorphic event was due to the northward subduction of Bangong-Nujiang Ocean beneath the Qiangtang terrane during late Triassic.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The suture zone is made up of a discontinuous belt of flysch, mélange and ophiolitic fragments (Kapp et al, 2003;B.D. Wang et al, 2016;K.J.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation